THE EFFECT OF PRICE DISCOUNT, BONUS PACK AND INSTORE DISPLAY ON IMPLUSE BUYING (CASE STUDY AT SUZUYA MALL MARELAN) - Cindy Kumala Dewi; Tuti Anggraini; Tri Inda Fadhila Rahma (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Modern retail stores are currently competing to provide the best service to attract more customers. One example is Suzuya Mall. Promotions are carried out for all products offered with various methods, such as price discounts, bonus packs and instore displays. The purpose of this study was to analyze the effect of price discounts, bonus packs, instore displays on impulse buying. On consumers at Suzuya Mall Marelan. Using a sample of 100 respondents and obtained using the Slovin Technique. With the data collection used in this study is a questionnaire. The results of the study showed that the price discount variable (X1) has a positive and significant effect on the impulse buying variable (Y) with a p-value of 0.014 (a=0.05). The bonus pack variable (X2) has a positive and significant effect on the impulse buying variable (Y) with a p-value of 0.000 (a=0.05). The in-store display variable (X3) has a positive and significant effect on the impulse buying variable (Y) with a p-value of 0.025 (a=0.05). price discount, bonus pack and in-store display have a simultaneous effect on impulse buying decisions at Suzuya Mall with a p-value of 0.000 (a=0.05).Keywords: price discount, in-store bonus pack and display on impulse buying